(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Electricity’s discovery and subsequent expansion over the previous few hundred years have firmly cemented its use and enhanced our dependency on it. This is since it is the most basic and cost-effective technique of carrying energy across large distances, and it is easy to convert into other forms such as mechanical motion or heat. As energy use rises and individuals who previously had access toelectricity become increasingly prepared to engage in the energy market, certain challenges arise. New infrastructure cannot be built in a place that is too remote from existing infrastructure and has a small population. In this situation, renewable energy sources such as micro hydro (if available),solar, and wind are the next best options. As the globe attempts to attain a carbon-neutral goal to minimize future damage caused by the use of fossil fuels, renewable energy sources are gaining in favor. This study provides a plausible idea for a tiny wind-powered microgrid for a small population in windy environments including mountainous regions and natural wind paths like valleys and mountain passes, large plains, and ocean locations, among others.